The Role of E-Government in Public Services: A Bibliometric Analysis - Didin Didin; Haedar Akib; Ahmad Wahidiyat Haedar; Alexsander Yandra (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2024)
This research investigates the pivotal role of e-government in public services through the lens of bibliometric analysis, employing the Biblioshiny tool for comprehensive bibliometric evaluation. E-government, a transformative force in contemporary public administration, involves the use of electronic platforms to deliver government services to citizens. The study employs bibliometric analysis to systematically examine and quantify the scholarly output, trends, and patterns in research related to the role of e-government in public services. The research leverages Biblioshiny, a sophisticated bibliometric analysis tool, to conduct an in-depth examination of a diverse range of publications. This tool facilitates the extraction of valuable insights from academic literature, shedding light on key thematic areas, prolific authors, and publication trends over specified periods. By employing bibliometric analysis, the study aims to provide a comprehensive overview of the intellectual landscape surrounding e-government in public services. The findings of this research are expected to contribute significantly to the understanding of the scholarly discourse on the role of e-government in public services. By utilizing bibliometric analysis, the study aims to identify gaps in existing research, highlight areas of prolific academic activity, and provide insights that can inform future research directions and policy considerations in the realm of e-government. Ultimately, this research endeavours to offer a nuanced and data-driven perspective on the evolving landscape of e-government and its impact on shaping effective and citizen-centric public services, thereby enhancing the efficiency, transparency, and accessibility of government operations and interactions with the public.